Non-destructive assessment of soluble solids content in kiwifruit using hyperspectral imaging coupled with feature engineering - Xu, Wei; Wei, Liangzhuang; Cheng, Wei; Yi, Xiangwei; Lin, Yandan (Frontiers in Plant Science, 2024)
The maturity of kiwifruit is widely gauged by its soluble solids content (SSC), with accurate assessment being essential to guarantee the fruit's quality. Hyperspectral imaging offers a nondestructive alternative to traditional destructive methods for SSC evaluation, though its efficacy is often hindered by the redundancy and external disturbances of spectral images. This study aims to enhance the accuracy of SSC predictions by employing feature engineering to meticulously select optimal spectral features and mitigate disturbance effects. We conducted a comprehensive investigation of four spectral pre-processing and nine spectral feature selection methods, as components of feature engineering, to determine their influence on the performance of a linear regression model based on ordinary least squares (OLS). Additionally, the stacking generalization technique was employed to amalgamate the strengths of the two most effective models derived from feature engineering. Our findings demonstrate a considerable improvement in SSC prediction accuracy post feature engineering. The most effective model, when considering both feature engineering and stacking generalization, achieved an 𝑅𝑅𝑅𝑅𝑅𝑅𝐸𝐸 𝑝𝑝 of 0.721, a 𝑅𝑅𝑀𝑀𝑀𝑀𝐸𝐸 𝑝𝑝 of 0.046, and an 𝑅𝑅𝑀𝑀𝐷𝐷 𝑝𝑝 of 1.394 in the prediction set. The study confirms that feature engineering, especially the careful selection of spectral features, and the stacking generalization technique are instrumental in bolstering SSC prediction in kiwifruit. This advancement enhances the application of hyperspectral imaging for quality assessment, offering benefits that extend across the agricultural industry.